Development and Performance Evaluation of a Thesis Circulation System for Graduate Studies at Thonburi University - Janthoom, Chainarong; Seesuay, Jantraporn; Pattasing, Atchara; Tanskul, Kawissara; Davis, Murray (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Study Circulation System for the Graduate School of Thonburi University, designed to replace traditional manual resource management with a secure and efficient digital platform. Utilizing the Agile Methodology for iterative development, the system was built as a web application using PHP and MySQL, with quality assessment conducted based on the ISO/IEC 25010 international standard.           The findings indicate exceptional technical performance, featuring an average search response time of 0.056 seconds and full-text (PDF) access time of 0.075 seconds, both of which significantly surpass international information system standards. Expert evaluation rated the system’s Functional Suitability and Reliability at a "Very High" level (µ = 4.73, σ = 0.159). Additionally, pilot testing with graduate students and administrative staff revealed a "High" level of user satisfaction, specifically regarding Operability (µ = 4.44, σ = 0.527).           The developed system successfully achieves a complete digital transformation of library management, enhances workflow efficiency through barcode integration, and protects intellectual property via a Secure Full-text Viewing feature, offering a replicable and high-performance model for graduate-level academic resource management.